2000
DOI: 10.1083/jcb.150.6.1461
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Pleckstrin Induces Cell Spreading via an Integrin-Dependent Pathway

Abstract: Pleckstrin is a 40-kD phosphoprotein containing NH2- and COOH-terminal pleckstrin homology (PH) domains separated by a disheveled-egl 10-pleckstrin (DEP) domain. After platelet activation, pleckstrin is rapidly phosphorylated by protein kinase C. We reported previously that expressed phosphorylated pleckstrin induces cytoskeletal reorganization and localizes in microvilli along with glycoproteins, such as integrins. Given the role of integrins in cytoskeletal organization and cell spreading, we investigated wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 26 publications
0
19
0
1
Order By: Relevance
“…PLEK (pleckstrin) plays an important role in proinflammatory cytokine activation (tumor necrosis factor α and IL1B) [46]. Its overexpression alters cytoskeletal organization and cell spreading [47]. It is less methylated and more expressed in MSE Endo versus ESE Endo and PE Endo , and also less methylated and more expressed in MSE Endo than MSE Control .…”
Section: Discussionmentioning
confidence: 99%
“…PLEK (pleckstrin) plays an important role in proinflammatory cytokine activation (tumor necrosis factor α and IL1B) [46]. Its overexpression alters cytoskeletal organization and cell spreading [47]. It is less methylated and more expressed in MSE Endo versus ESE Endo and PE Endo , and also less methylated and more expressed in MSE Endo than MSE Control .…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Heterologous expression studies show that pleckstrin can reorganize the actin cytoskeleton. 27,28,36 Because the available evidence suggests that disassembly of F-actin facilitates exocytosis in platelets, it is possible that pleckstrin indirectly links PKC with exocytosis by facilitating F-actin reorganization. Therefore, we analyzed the ability of pleckstrinnull platelets to increase their levels of F-actin in response to PMA.…”
Section: Pleckstrin and Actin Assemblymentioning
confidence: 99%
“…[23][24][25][26] Overexpression and microinjection studies suggest that pleckstrin is membrane localized, induces a shift of F-actin toward the cell cortex, and participates in the production of lamellipodia. 27,28 Those studies of cultured cell lines further suggest that pleckstrin induces these cellular changes through a signaling pathway that involves phospholipids, integrins, and small GTP-binding proteins of the Rho family. 29 These responses are tightly regulated by PKC-mediated phosphorylation of 3 residues in pleckstrin (Ser113, Thr114, and Ser117), located immediately after the amino-terminal PH domain.…”
Section: Introductionmentioning
confidence: 99%
“…Because expression of pleckstrin-1 enhances cell spreading within adherent cell lines, 26,27 we analyzed whether pleckstrin-2 affected Jurkat T-cell spreading by quantifying the footprint sizes of Jurkat T cells overexpressing wild-type pleckstrin-2 or pleckstrin-2 mutants. We found that when pleckstrin-2-expressing Jurkat cells were nonspecifically adhered to poly-L-lysine-coated plates, there were only small changes in the cell-footprint size ( Figure 2C).…”
Section: Expression Of Pleckstrin-2 In Jurkat Cells Increases Cell Spmentioning
confidence: 99%
“…25 Pleckstrin-1 induces cell spreading and reorganization of the actin cytoskeleton. 26,27 These pleckstrin-1-mediated effects are entirely regulated by its phosphorylation state. Because pleckstrin-2 does not appear to be a phosphoprotein, we reasoned that its interaction with its binding partners or intracellular localization regulates its activity.…”
Section: Introductionmentioning
confidence: 99%